Analysis Of The Implementation Of The Marketing Strategy Of Kokita Cooking Seasoning Products In PT. Ikafood Putramas - Adrian Hijrah Kusuma; Slamet Heri Winarno; Irwan Raharja (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
In business competition where more and more competitors are emerging, marketing strategies are used to attract consumers' attention. The better the strategy used will greatly affect the level of product sales offered by the company. As one of the companies in Indonesia, PT. Ikafood Putramas must be smart and astute in choosing marketing strategies to develop companies in the business world. This study aims to determine the marketing strategy of kokita 4p products (product, place, price, and promotion) at PT. Ikafood Putramas and knowing the obstacles and looking for solutions faced in the kokita product of PT. Ikafood Putramas. Analysis of the data used in this research is by using qualitative descriptive analysis, where the purpose of this analysis is to describe a systematic, factual and accurate. Data analysis consisted of data reduction, data presentation and conclusion drawing. Data were collected through observation and interviews with the area manager of PT. Ikafood Putramas. The results of the study concluded that the marketing strategy used by PT. Ikafood Putramas is a marketing strategy oriented to the 4P theory (Product, Price, Place, Promotion) as the basis of their marketing strategy, by creating a variety of products, setting prices according to product grammar, distributing products to consumers, and conducting promotions using salesmen. and also use advances in technology.